Valoración De La Condición Física De Los Estudiantes De Educación Física De Primer Semestre 2013 (2014)
The research was to identify the physical condition of undergraduates in physical education from first half of the University of Quindío, which comprise the ages of 15-31 years of age, for a total of 75 students. The variables studied were: explosive strength, speed, flexibility and VO2 max. The research was descriptive transversely. Where a univariate analysis of each feature using measures of central tendency was used. The highlight of this study was that the students tested had a physical condition not according to the requirements and needs of a student of physical education, where 70% of those who entered the program of physical education show a flexibility assessment fair to wrong. In addition, 64% of men and 76% of women have a maximum oxygen consumption fair to poor. Interestingly women have similar flexibility than men, which is contradictory with regard morpho functional basics. Also presented, the explosive force is the only variable in which the largest percentage of the study population is between good and excellent.